Industrial Policy and Firm Heterogeneity - Barros, Pedro Pita (2019)
Our concern is about a firm-specific industrial policy. When R&D subsidies or taxes are differentiated among firms, the question arises which firms in an industry should receive such support. We analyze a situation where firms differ in their R&D to in two distinct ways. They differ both in the costs of performing R&D activities and in the output obtained from such activities. The introduction of several domestic firms creates a corrective motive for government intervention with the firms' R&D activities in addition to Spencer and Brander's strategic motive. We find that the optimal firm-specific industrial policy. is affected differently by the two sources of firm heterogeneity. Another finding is that a change in a firm's R&D productivity has an ambiguous effect on the optimal policy towards the firm.